A comparative study between two triclosan containing toothpastes on plaque regrowth and gingivitis - Aguirre, Rodel; Sanchez, Noel.; Vergel de Dios, Nanette (Adviser).
The aim of the present clinical trial was to study the effectiveness of triclosan containing toothpastes on plaque regrowth and gingivitis for one week period of no oral hygiene. Thirty subjects selected through random sampling were selected for the trial. After thorough scaling and polishing, the subjects were randomly divided into three equal groups and were assigned the following treatment: 1 test group used a triclosan containing toothpaste only, 1 test group used a toothpaste which has triclosan and allantoin, and 1 control group which used a toothpaste containing sodium monoflourophosphate (placebo). The participants were instructed to rinse for 1 minute with a toothpaste slurry made up of 1 inch toothpaste dissolved in 10 ml of water 3 x a day in the absence of any other form of oral hygiene procedures. After 1 week, the subjects were examined for plaque and gingivitis using the criteria of i) Turesky's modification of Quigley and Hein plaque index and ii) Loe and Silness gingival index. Six control teeth were used (16,26,11,36,31,46) and plaque and gingivitis were assessed at 6 location points around the tooth. The findings from the examination revealed a significant difference between the triclosan containing toothpaste and from the control group. However, there is no significant difference among the two triclosan containing toothpaste on plaque regrowth and gingivitis.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gingivitis; Dental plaque; Dentifrices -- Evaluation; Triclosan